Clinical Characteristics And Radiological Features Of Multi-Drug-Resistant (MDR) Pulmonary TB Patients - Andi Irgi Ahmad Fahrezi; Febie Irsandy; Harry Azka (Jurnal EduHealth, 2024)
Tuberculosis is currently still a public health problem both in Indonesia and internationally, so it has become one of the goals of sustainable health development.WHO estimates that 10 million people suffer from pulmonary tuberculosis (TB) and it caused 1.4 million deaths in 2019. Multidrug Resistant Tuberculosis (MDR-TB) is a type of tuberculosis that is resistant to at least two first-line antibiotics. This study uses the Literature Review method with a Narrative Review design to identify and summarize previously published articles regarding the clinical characteristics and radiological features of mult-drug-resistant pulmonary TB patients. From the results it was found that there was a relationship between clinical characteristics and radiological features of mult-drug-resistant pulmonary TB patients, the emergence of MDR-TB did not only indicate that the treatment strategy had failed; MDR-TB itself can be a barrier to anti-tuberculosis treatment. So clinical-radiological characteristics should always be determined where appropriately administered drugs have not reached the levels necessary to treat all mycobacterial populations, in order to modify and strengthen national programs in a timely manner, and evaluate trends in drug resistance patterns